Atypical Presentation of Severe Dengue in a Patient following a Major Abdominal Surgery. (10th August 2020) - Jayarajah, Umesh; Basnayake, Oshan; Nagodavithane, Kavinda; Jayasinghe, Jayan; Samarasekera, Dharmabandhu N.
Abstract : Severe dengue infections in a postoperative patient may lead to significant derangement in the body's homeostasis resulting in morbidity and sometimes even mortality. Reports on presentation and clinical manifestations of dengue in patients following major surgical procedures are scarce and restricted to few case reports. We describe a 26-year-old male with atypical presentation and late detection of dengue haemorrhagic fever following a major abdominal surgery. On postoperative day 6, he developed spontaneous bleeding from the drain site and moderate-to-massive bilateral pleural effusion with respiratory distress. His dengue IgM and IgG were positive. Therefore, a diagnosis of dengue haemorrhagic fever with bilateral lower zone pneumonia was made. A right-sided intercostal tube was inserted. Intensive care was given and was managed with intravenous antibiotics, targeted fluid therapy, and supportive care. He recovered from the infection and was discharged uneventfully. This case is unique because during the postoperative period, he went into critical phase with significant fluid leakage and developed bleeding manifestations without a clear febrile phase and deterioration in the haemodynamic parameters. High degree of suspicion and early detection are necessary to guide the fluid therapy and provide organ support in such patients.